The Influence of Genotype and Environment on Small RNA Profiles in Grapevine Berry - Paim Pinto, Daniela Lopes; Brancadoro, Lucio; Dal Santo, Silvia; De Lorenzis, Gabriella; Pezzotti, Mario; Meyers, Blake C.; Pè, Mario E.; Mica, Erica (Frontiers in Plant Science, 2016)
Understanding the molecular mechanisms involved in the interaction between the genetic composition and the environment is crucial for modern viticulture. We approached this issue by focusing on the small RNA transcriptome in grapevine berries of the two varieties Cabernet Sauvignon and Sangiovese, growing in adjacent vineyards in three different environments. Four different developmental stages were studied and a total of 48 libraries of small RNAs were produced and sequenced. Using a proximity-based pipeline, we determined the general landscape of small RNAs accumulation in grapevine berries. We also investigated the presence of known and novel miRNAs and analyzed their accumulation profile. The results showed that the distribution of small RNA-producing loci is variable between the two cultivars, and that the level of variation depends on the vineyard. Differently, the profile of miRNA accumulation mainly depends on the developmental stage. The vineyard in Riccione maximizes the differences between the varieties, promoting the production of more than one thousand specific small RNA loci and modulating their expression depending on the cultivar and the maturation stage. In total, 89 known vvi-miRNAs and 33 novel vvi-miRNA candidates were identified in our samples, many of them showing the accumulation profile modulated by at least one of the factors studied. The in silico prediction of miRNA targets suggests their involvement in berry development and in secondary metabolites accumulation such as anthocyanins and polyphenols.